THE SECURITIES ISSUER FINANCIAL CAPACITY FORMATION UNDER THE CONDITIONS OF COUNTRY INTEGRATION INTO THE WORLD FINANCIAL SPACE - PYLYPENKO, Andriy; POPOV, Oleksandr; HRYHORASH, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article highlights the features of the securities issuer's financial capacity formation. It explores the tools for this capacity development under the conditions of expanding economic entities' access to the global financial space resources. This study aims to advance the theoretical and methodological foundations for shaping the financial potential of securities issuers and to identify the peculiarities of the institutional development of financial potential in the context of Ukraine's integration into the global financial arena. The possibility to use a financial space’s system breakdown structure for establishing the subordinate level financial capacity by taking into account the requirements to the higher-level financial capacity has been presented as a hypothesis of the study. The relevance of reorienting the processes of financial capacity formation to promote the emergence effects appearance between the hierarchical levels of the country's financial space has been justified and presented as part of the proof of article hypothesis implementation. The logic behind the systematic segmentation of a country's financial space has been unveiled to determine the influence of its integration processes into the global financial arena on the capability of securities issuers to cultivate financial potential. The emergent interrelation with financial resources has been elucidated for each identified type of potential (resource, production, labor, innovation, social, organizational management, and financial). It has been demonstrated that the formation and development of the financial potential of securities issuers can only occur when taking into account all higher levels of the systematic segmentation of the state's financial space. Emergence has been presented as a basis for improving the institutional support of securities issuers’ financial capacity formation and development.
Keywords: financial capacity; securities issuers; capacity formation; world financial space; emergence